Absorbable hemostatic bone graft material and preparation method thereof
By developing a composite material containing mineralized collagen complex, polyethylene glycol and sodium carboxymethylcellulose, the problem of non-degradability and insufficient biocompatibility of existing bone wax materials has been solved, and effective hemostasis and bones have been achieved. Healing and biodegradation reduces the risk of foreign body reaction, simplifies the preparation process and reduces costs.
Patent Information
- Application Number
- CN202411781243.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-02-14
AI Technical Summary
The existing bone wax materials are non-degradable, interfere with bone healing, lack biocompatibility, insufficient hemostasis effect, insufficient support for bone healing, and complex preparation process and high cost.
Develop a composite material containing mineralized collagen complex (MCC), polyethylene glycol (PEG), and sodium carboxymethylcellulose (CMC), which is formed by depositing bionic mineralized apatite on collagen fibers. Combining the properties of PEG and CMC, it provides effective hemostasis, promotes bone healing, and biodegradation over time.
This material can effectively control bleeding, promote bone cell proliferation and differentiation, support natural bone healing, and biodegradation over time, avoid foreign body reactions and chronic inflammation, and reduce preparation costs and process complexity.
Abstract
Description
Technical Field
[0001] The invention relates to the field of biomaterials and medical devices, in particular to an absorbable hemostatic bone transplant material. Background Art
[0002] Controlling bleeding and promoting bone healing are critical during surgical procedures, especially orthopedic, neurosurgery, and dental procedures. Traditional bone wax, composed of non-resorbable materials such as beeswax and paraffin, while effective in providing temporary hemostasis, has significant disadvantages. These traditional materials remain in the surgical site indefinitely, interfering with natural bone healing, promoting inflammation, and carrying the risk of foreign body reaction or infection. In addition, non-degradable bone wax forms a physical barrier that impedes bone formation, delaying recovery, and in some cases requiring surgical removal.
[0003] To overcome these limitations, resorbable bone wax and bone graft materials have been developed, aiming to combine the advantages of hemostasis and bone regeneration without the need for removal. However, current resorbable substitutes often lack in mechanical strength, biocompatibility, or hemostatic properties. There is a pressing need for a material that not only effectively controls bleeding but also integrates with surrounding bone tissue and supports natural bone healing while biodegrading over time.
[0004] Problems 1. The non-degradability of existing bone wax: Bone wax with beeswax as the main component is left at the surgical site, which may interfere with the bone healing process and cause chronic inflammatory response.
[0005] 2. Lack of biocompatibility: Many existing bone graft materials have poor compatibility with human tissues and may cause adverse immune responses or infections.
[0006] 3. Insufficient hemostatic effect: Some biodegradable hemostatic materials lack rapid and effective hemostatic ability and cannot meet the needs of rapid hemostasis during surgery.
[0007] 4. Insufficient support for bone healing: Existing bone transplant materials may lack the necessary bioactive components and cannot effectively promote the proliferation and differentiation of bone cells, resulting in slow bone healing.
[0008] 5. The preparation process of the raw collagen used for bone transplant materials takes a long time and has a complicated process. Although bone repair materials made of bionic mineralized collagen fibers have been widely used in clinical practice, their adhesion ability is weak and they are not suitable for use as hemostatic bone transplant materials. They are prone to disintegration in clinical practice, and their adhesion ability is weak when encountering large blood flow, which affects their clinical application. Summary of the invention
[0009] The present invention provides an absorbable hemostatic bone graft material for use in surgery, which is a composite material comprising a mineralized collagen complex (MCC), polyethylene glycol (PEG) and sodium carboxymethyl cellulose (CMC), the material being intended to provide effective hemostasis while promoting bone healing and biodegrading over time. The preparation method comprises treating collagen fibers with biomimetic mineralized apatite to form a mineralized collagen complex, heating and melting PEG and mixing the mineralized collagen complex and CMC to form a matrix, and molding and curing the mixture into a desired shape, and also comprises a method for preparing a mineralized collagen complex using pig skin and cow skin as raw materials, and a method for depositing biomimetic mineralized apatite on collagen fibers by controlling the pH value.
[0010] Technical solution:
[0011] (1) Material composition: Mineralized collagen complex (MCC): as a structural matrix to promote bone regeneration. The composition and structure of the natural bone extracellular matrix are simulated by compounding biomimetic mineralized apatite in the fibers formed by collagen. The mineralized collagen complex is formed by in situ deposition of biomimetic mineralized apatite on collagen fibers. The average particle size of the biomimetic mineralized apatite crystals is 50-300nm and is tightly combined with the collagen fibers. The collagen fibers are prepared from pig skin and cow skin.
[0012] Polyethylene glycol (PEG): As a dispersant that provides flexible shaping properties and adjustable degradability, it provides flexibility to the material and controls the degradation rate of the material by adjusting its molecular weight. The polyethylene glycol is a mixture of low molecular weight polyethylene glycol and high molecular weight polyethylene glycol, wherein the molecular weight of the low molecular weight polyethylene glycol is 400~600Da, and the molecular weight of the high molecular weight polyethylene glycol is 1000~4000Da. The mass ratio of the two polyethylene glycols is 1:2~1:5 to provide controllable biodegradability. The degradation rate 24~48h after use can be adjusted by the molecular weight and composition ratio of the PEG used.
[0013] Sodium carboxymethyl cellulose (CMC): As a gel-forming agent, combined with mineralized collagen complexes, it provides further blood-absorbing ability. The combination of collagen and calcium salts can trigger a coagulation cascade reaction, achieving immediate hemostasis when applied to a bleeding bone surface. The viscosity of sodium carboxymethyl cellulose (2% aqueous solution) is selected to be 300 to 3000 mPa·s.
[0014] In order to ensure the plasticity and adhesion properties of the material, the mass ratio of MCC to PEG is in the range of 1:1~1:15, and the mass of CMC accounts for 5~20% of the total composition.
[0015] (2) Preparation method: The biomimetic mineralized apatite is formed by reacting with collagen in a solution containing calcium and phosphate ions, and then the pH value is adjusted within the range of 9 to 12 to deposit the biomimetic mineralized apatite on the collagen fibers, and then the biomimetic mineralized apatite is obtained after washing, freeze-drying and crushing. Subsequently, pig skin and cowhide are used as raw materials, and the collagen fibers are compounded with the biomimetic mineralized apatite to form a mineralized collagen complex.
[0016] The mineralized collagen complex and CMC are mixed with the melted PEG in powder form and mixed and stirred evenly at a certain temperature to form a mixture with the required flexibility and mechanical strength.
[0017] Molding and curing: The resulting mixture is repeatedly kneaded and shaped into the desired shape or form, shaped into sheets, or added with water or thermosensitive gel to form a paste or ointment.
[0018] The hemostatic bone graft material is obtained by packaging and sterilizing. The sterile treatment adopts radiation sterilization, including but not limited to electron beam and gamma ray.
[0019] (3) Application The bone graft material is suitable for a variety of surgical procedures, including but not limited to orthopedic surgery, neurosurgery and dental surgery. The bone graft material is applied to the bleeding bone surface during orthopedic, neurosurgery or spinal surgery; the material is allowed to adhere to the bleeding site, provide hemostasis and support bone regeneration.
[0020] The material is designed to be resorbable, and its degradation rate can be controlled by adjusting the molecular weight and cross-linking density of PEG to suit different clinical needs, allowing the material to biodegrade over time while being replaced by new bone tissue.
[0021] The technical solution provided herein also includes a method for preparing an absorbable hemostatic bone graft material, comprising the following steps: (1) Mineralized collagen composite, using pig skin and cow skin as raw materials, preparing collagen fibers through alcohol washing, alkali washing, acid washing, enzymatic hydrolysis, salting out and alcohol washing series treatment, and blending with biomimetic mineralized apatite to form a mineralized collagen composite; (2) forming a matrix by heating to melt PEG and form a flexible, absorbable matrix with mineralized collagen complex fibers; (3) adding sodium carboxymethylcellulose (CMC) to enhance the hemostatic and adhesive properties by mixing CMC into the mineralized collagen complex-PEG matrix; (4) Molding and curing: the mixture is repeatedly kneaded and shaped into a desired shape or form, and then formed into a sheet, or water or thermosensitive gel is added to form a paste or ointment for use as a bone transplant material or bone wax.
[0022] In the above preparation method, the step of mineralizing the collagen complex comprises the following steps: (1) Mix the defatted skin slices (1-2 cm square slices) with isopropyl alcohol in a mass ratio of 1:10-1:50, stir and dehydrate for 1-2 hours, and drain to obtain the dehydrated skin; (2) Add the dehydrated skin to 1-4% sodium hydroxide solution and stir for alkali treatment for 1-2 hours, drain, and repeat this step twice to obtain alkali-treated skin; (3) Add the alkali-treated leather into a 0.1 M acetic acid solution and stir for 1 to 2 hours, then drain to obtain the acidified leather; (4) mixing the acidified leather with purified water in a mass ratio of 1:20, cooling to 2-8°C, and mechanically crushing to obtain a slurry; (5) Add 0.2-2 g of pepsin per 1 L of the slurry, adjust the pH to 2-3, and perform enzymatic hydrolysis at a temperature of 4-25 °C; (6) After the enzymatic hydrolysis is completed, the pH is adjusted to neutral to obtain a collagen solution, which is added to a 20% sodium chloride solution and stirred. The salting-out product is filtered and the filter cake is taken to obtain a crude collagen product; (7) Add the crude collagen to 0.1 M acetic acid solution and stir to dissolve, then add it to 20% sodium chloride solution and stir again, filter the salting-out product, and take the filter cake to obtain the secondary salting-out collagen wet product; (8) adding the secondary salting-out collagen wet product into a 50-80% ethanol solution, adding biomimetic mineralized apatite in a mass ratio of 1:5-1:1 to the filter cake, and stirring to form mineralized collagen composite fibers; (9) Packing the mineralized collagen complex fibers into freeze-drying molds, pre-freezing at -10 to -20°C, and freeze-drying to obtain block-shaped mineralized collagen complexes; (10) The block-shaped mineralized collagen complex is subjected to vacuum heat cross-linking treatment at 105-140° C. for 2-24 h, and after cooling, it is taken out and mechanically crushed, and sieved to obtain a powdered mineralized collagen complex.
[0023] Pig skin and cowhide are used as raw materials. After alkali treatment, acid treatment, enzymatic hydrolysis and salting out treatment, they are stirred with biomimetic mineralized apatite in 50~80% ethanol solution to form collagen composite fibers. Compared with traditional solution blending, this treatment method accelerates the precipitation rate of collagen composite fibers and improves the binding ability of collagen fibers and biomimetic mineralized apatite.
[0024] In the preparation steps of the above-mentioned hemostatic bone graft material, the biomimetic mineralized apatite is prepared by reacting with collagen in a solution containing calcium and phosphate ions, and then the pH value is adjusted within the range of 9 to 12 to deposit the biomimetic mineralized apatite on the collagen fibers, and the biomimetic mineralized apatite is obtained after washing, freeze-drying and crushing. Commercially available apatite can also be used, and the particle size is preferably 100 nm or less.
[0025] In the preparation steps of the above-mentioned hemostatic bone graft material, the step of forming the matrix is achieved by melting polyethylene glycol (PEG) and mixing and dispersing the mineralized collagen complex at a temperature of 40-60°C for 10 minutes to 24 hours, depending on the material ratio and the dispersion device.
[0026] In the preparation steps of the above hemostatic bone graft material, sodium carboxymethylcellulose (CMC) is added in powder form to ensure uniform distribution throughout the mixture, and the final composition is sterilized before use.
[0027] This absorbable hemostatic bone graft material can be blended with thermosensitive polymers (such as poloxamer F127), growth factors, osteogenic induction proteins, antibacterial agents or bioactive agents selected from their combination to form a composition to enhance the effect of promoting bone healing and preventing infection after the material is implanted. After being added, the thermosensitive polymer can play the role of sustained release of drugs, such as growth factors or antibiotics, and in the in vivo environment, it exhibits gel properties, improves mechanical properties, and increases adhesion and flexibility.
[0028] This innovative combination of absorbable hemostatic bone graft material offers several significant advantages: (1) Promote bone regeneration: The mineralized collagen complex mimics the natural bone matrix, providing an osteogenic guiding scaffold that promotes bone cell attachment, proliferation, and differentiation. By incorporating biomimetic mineralized apatite minerals into the collagen matrix, the material supports the regeneration of new bone tissue while gradually biodegrading, allowing natural bone healing to proceed unhindered.
[0029] (2) Enhanced hemostatic properties: Mineralized collagen complexes, due to their nano-bionic mineralized apatite properties, are very easy to interact with platelets in the blood and have a strong coagulation effect; CMC is well-known for its excellent gel-forming and hemostatic properties. When in contact with blood, the CMC component rapidly expands and forms a gel, effectively sealing the bleeding surface and promoting the formation of blood clots.
[0030] (3) Biodegradability: Unlike traditional bone wax that persists at the surgical site, the bone graft material of the present invention biodegrades over time and is gradually replaced by new bone. This eliminates the need for secondary surgery to remove residual material and minimizes the risk of foreign body reaction or chronic inflammation.
[0031] (4) Customizable mechanical properties: Using PEG as a dispersant, the mechanical strength and degradation rate can be adjusted. By adjusting the molecular weight and cross-linking density of PEG, the flexibility, durability, and absorption time of the material can be customized for specific surgical needs.
[0032] (5) Improved biocompatibility: All components—mineralized collagen complex, PEG, and CMC—are biocompatible and widely used in medical applications. This ensures good integration of the material with surrounding tissues, reduces the risk of adverse reactions or complications, and promotes rapid recovery for patients.
[0033] (6) Potential for additive functionality: Material design allows for the incorporation of additional bioactive agents, such as thermosensitive polymers, growth factors, osteoinductive proteins, or antimicrobial agents. These additives can further enhance bone healing, accelerate recovery, or reduce the risk of postoperative infection, providing multifunctional solutions for complex surgical situations.
[0034] (7) Mineralized collagen complexes were prepared using pig skin and cow skin as raw materials. The preparation method has compact steps. By combining the process flow of alcohol washing, alkali treatment, acid treatment, enzyme treatment and ethanol treatment, the treatment and separation and purification were optimized. The bionic mineralized apatite composite treatment was combined with solvent treatment, which effectively reduced the manufacturing cost. The manufacturing process of mineralized collagen can be shortened from the traditional 40 to 50 days to 10 to 20 days, greatly reducing the production cost. DETAILED DESCRIPTION
[0035] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] Embodiment 1: Preparation of biomimetic mineralized apatite (BGHA-01) Material: (1) Type I collagen: 4.0g (2) Anhydrous calcium chloride: 175.0 g (3) Phosphoric acid: 105.0 g (85%) (4) Sodium hydroxide: 160.0 g step: 1. Preparation of collagen solution: Weigh 4.0 g of type I collagen, dissolve it in 4 L of purified water, and stir until it is completely dissolved to form a uniform collagen solution.
[0037] 2. Solution preparation: Dissolve 175.0 g of anhydrous calcium chloride in 1500 ml of purified water and stir until completely dissolved to obtain a calcium chloride solution; dissolve 105.0 g of 85% phosphoric acid in 900 ml of purified water and stir until completely dissolved to obtain a phosphoric acid solution; dissolve 160.0 g of sodium hydroxide in 1000 ml of purified water and stir until completely dissolved to obtain a sodium hydroxide solution.
[0038] 3. Precipitation reaction of biomimetic mineralized apatite: Slowly add calcium chloride solution to collagen solution and stir continuously to ensure uniform mixing. Add phosphoric acid solution and stir continuously. Use sodium hydroxide solution to adjust pH to 11-11.5 and keep the mixed solution at 37°C overnight to promote the formation of biomimetic mineralized apatite.
[0039] 4. Cleaning: After 16 hours, the supernatant was poured off and fresh purified water was added to wash to remove unreacted reagents and byproducts. The washing step was repeated 4 times, stirring for 5 minutes each time and then allowed to settle to ensure thorough washing.
[0040] 5. Filtration and freeze drying: The precipitate is separated by filtration to obtain a filter cake, which is pre-frozen and then freeze-dried in a freeze dryer to obtain biomimetic mineralized apatite (BGHA-01).
[0041] 6. Drying and crushing: The freeze-dried biomimetic mineralized apatite (BGHA-01) was further dried and crushed and sieved to obtain powder with the desired particle size (60 mesh).
[0042] Embodiment 2: Preparation of mineralized collagen complex fiber powder (BGHA-02) Material: (1) Degreased pig skin: 200.0g (2) Isopropyl alcohol: 2000ml (3) Sodium hydroxide: 40.0 g (4) Acetic acid: 36.0 g (5) Pepsin (1:10000NF): 1.0g (6) Bionic mineralized apatite (BGHA-01): 12.0g step: 1. Dehydration treatment: 200.0 g of degreased pig skin was cut into small pieces, added into 2000 ml of isopropanol, stirred and dehydrated for 2 hours, and drained to obtain dehydrated skin.
[0043] 2. Alkali treatment: Use 40.0g of sodium hydroxide to prepare a 2% solution, add the dehydrated skin into it, stir and degrease for 1 hour, drain, repeat this step twice to obtain alkali-treated skin.
[0044] 3. Acidification treatment: Dissolve 12.0 g of acetic acid in 2000 ml of purified water, add defatted pig skin into the acetic acid solution and stir for 1 hour, then drain to obtain acidified skin.
[0045] 4. Enzymatic treatment: The acidified skin was added into 4 L purified water, cooled to 2-8 °C, and mechanically crushed to obtain slurry.
[0046] 1.0 g of pepsin (1:10000 NF) was added to the slurry, the pH was adjusted to 2-3, and the enzymatic treatment was performed at room temperature for 4 hours.
[0047] After the enzymatic hydrolysis is completed, the pH is adjusted to neutral to obtain a collagen solution.
[0048] 5. Salting out treatment: 800.0 g of sodium chloride was dissolved in 4 L of purified water, the collagen solution was added thereto and stirred, the salting-out product was filtered, and the filter cake was taken to obtain the crude collagen.
[0049] 6. Dissolution and secondary salting out: 24.0 g of acetic acid was dissolved in 4 L of purified water, and crude collagen was added thereto and stirred to dissolve. 400.0 g of sodium chloride was dissolved in 4 L of purified water, and collagen solution was added thereto and stirred, and the salting out product was filtered, and the filter cake was taken to obtain a secondary salting out collagen wet product.
[0050] 7. Washing and mineralization: The filter cake was added into a 60% ethanol solution prepared by 1200 ml of ethanol and 800 ml of purified water and stirred for washing. 12.0 g of biomimetic mineralized apatite (BGHA-01) was added and stirred to form a mineralized collagen complex.
[0051] 8. Freeze-drying and cross-linking: The mineralized collagen complex fibers were divided into freeze-drying molds, pre-frozen at -10°C, and freeze-dried to obtain block-shaped mineralized collagen complexes. The block-shaped mineralized collagen complexes were subjected to vacuum heat cross-linking treatment at 105°C for 2 hours.
[0052] 9. Crushing and screening: After cooling, the mixture was taken out and mechanically crushed, and sieved to obtain powdered mineralized collagen complex MCC (BGHA-02) (12 mesh).
[0053] Embodiment 3: Weigh 12.0 g PEG 1500 and 3.0 g PEG 400, heat to 60°C to melt, then add 1.0 g powdered mineralized collagen complex MCC (Example 2, BGHA-02) and 4.0 g sodium carboxymethyl cellulose (300-800 mPa·s) in sequence, stir and mix thoroughly. After cooling to room temperature, knead and mix repeatedly, cut and package, and sterilize by Co60 radiation (25 kGy) to prepare hemostatic bone transplant material.
[0054] Example 4 Weigh 12.0g PEG 1500 and 3.0g PEG 400, heat to 60°C to melt, then add 2.5g powdered mineralized collagen complex MCC (Example 2, BGHA-02) and 2.5g sodium carboxymethyl cellulose (300-800 mPa·s) in sequence, stir and mix thoroughly. After cooling to room temperature, knead and mix repeatedly, cut and package, and sterilize by Co60 radiation (25kGy) to prepare hemostatic bone transplant material.
[0055] Example 5 Weigh 18.0g PEG 1500 and 4.5g PEG 400, heat to 60°C to melt, then add 5.0g powdered mineralized collagen complex MCC (Example 2, BGHA-02), 2.0g sodium carboxymethyl cellulose (300-800 mPa·s), stir and mix thoroughly, then add 2.0g poloxamer F127 and mix thoroughly. After cooling to room temperature, knead and mix repeatedly, cut and package, and sterilize by Co60 radiation (25kGy) to prepare hemostatic bone transplant material.
[0056] Simulated bone filling test The material of the above embodiment was molded into a proper shape and inserted into the gap of the model to simulate the clinical filling of bone gaps to stop bleeding, and then flushed with running water. The results showed that the material of the above embodiment had excellent resistance to running water flushing and the adhesion performance met the clinical application requirements.
[0057] Simulated degradation test The above-mentioned example materials were cut into small pieces of appropriate size and immersed in 37°C saline for 48 hours. It was observed that: Example 3: No obvious change after 2 hours, gradually swelled into a sponge-like state after 3 hours, dissolved a small amount, no dispersion after 7 hours, and covered with a layer of translucent gel-like substance on the surface after 48 hours, with the height basically unchanged.
[0058] Example 4: No obvious change after 2 hours, gradually swelled into a sponge-like state after 3 hours, partially dissolved, a small amount of scattered fibers after 7 hours, fibers visible on the surface, and a layer of translucent gel-like substance covering the surface after 48 hours, with the height remaining basically unchanged.
[0059] Example 5: There was no obvious change after 2 hours. After 3 hours, it changed from a paste to a sponge and was partially dissolved. After 48 hours, the surface was covered with a layer of translucent gel-like substance, and the height remained basically unchanged.
[0060] The above-mentioned simulated degradation test verifies the degradation performance of the hemostatic bone graft material in body fluids, in which low molecular weight PEG dissolves to form a spongy osteogenic structure encapsulating CMC gel. PEG dissolves to form a porous structure, while exposing MCC to provide osteogenic activity, promote the growth, proliferation and differentiation of bone cells, and thus accelerate bone tissue repair and healing.
[0061] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An absorbable hemostatic bone graft material, comprising the following composition: (1) Mineralized collagen complex (MCC), as a structural matrix for bone regeneration; (2) Polyethylene glycol (PEG), as a dispersant that provides flexible shaping properties and tunable degradability; (3) Sodium carboxymethylcellulose (CMC), as a gel-forming agent, is used to enhance hemostatic properties and adhesive ability; The mass ratio of MCC to PEG ranges from 1:1 to 1:15, and the mass of CMC accounts for 5 to 20% of the total composition.
2. The absorbable hemostatic bone graft material according to claim 1, wherein the mineralized collagen complex is formed by in situ deposition of biomimetic mineralized apatite on collagen fibers, the average particle size of the biomimetic mineralized apatite crystals is 50-300 nm, and the biomimetic mineralized apatite crystals are tightly combined with the collagen fibers, and the collagen fibers are prepared from pig skin and cow skin as raw materials.
3. The absorbable hemostatic bone graft material according to claim 1, wherein the polyethylene glycol is a mixture of low molecular weight polyethylene glycol and high molecular weight polyethylene glycol, wherein the molecular weight of the low molecular weight polyethylene glycol is 400-600 Da, the molecular weight of the high molecular weight polyethylene glycol is 1000-4000 Da, and the mass ratio of the two polyethylene glycols is 1:2-1:5, so as to provide controllable biodegradability, and the degradation rate within 24-48 hours after use can be adjusted by the molecular weight and composition ratio of the PEG used.
4. The absorbable hemostatic bone graft material of claim 1, wherein sodium carboxymethyl cellulose is used as a gel forming agent in combination with a mineralized collagen complex to provide further blood absorbing ability, and the combination with collagen and calcium salt can trigger a coagulation cascade reaction, thereby achieving immediate hemostasis when applied to a bleeding bone surface, and the viscosity of sodium carboxymethyl cellulose (2% aqueous solution) is selected to be 300 to 3000 mPa·s.
5. A method for preparing an absorbable hemostatic bone graft material, comprising the following steps: (1) Preparation of MCC: using pig skin and cow skin as raw materials, preparing collagen fibers through alcohol washing, alkali washing, acid washing, enzymatic hydrolysis, salting out and alcohol washing series treatment, and mixing with biomimetic mineralized apatite to prepare MCC; (2) Forming a matrix by heating to melt PEG and form a rapidly absorbable matrix with MCC; (3) CMC was added to enhance the hemostatic and adhesive properties by mixing CMC into the MCC-PEG matrix; (4) shaping and curing, wherein the mixture is repeatedly kneaded and shaped into a desired shape or form, and then shaped into a sheet, or water or a thermosensitive gel is added to form a paste or ointment; (5) Packaging and sterilization.
6. The method of claim 5, wherein the step of preparing MCC comprises the following steps: (1) Mix the defatted skin slices (1-2 cm square slices) with isopropyl alcohol in a mass ratio of 1:10-1:50, stir and dehydrate for 1-2 hours, and drain to obtain the dehydrated skin; (2) Add the dehydrated skin to 1-4% sodium hydroxide solution and stir for alkali treatment for 1-2 hours, drain, and repeat this step twice to obtain alkali-treated skin; (3) Add the alkali-treated leather into a 0.1 M acetic acid solution and stir for 1 to 2 hours, then drain to obtain the acidified leather; (4) mixing the acidified leather with purified water in a mass ratio of 1:20, cooling to 2-8°C, and mechanically crushing to obtain a slurry; (5) Add 0.2-2 g of pepsin per 1 L of the slurry, adjust the pH to 2-3, and perform enzymatic hydrolysis at a temperature of 4-25 °C; (6) After the enzymatic hydrolysis is completed, the pH is adjusted to neutral to obtain a collagen solution, which is added to a 20% sodium chloride solution and stirred. The salting-out product is filtered and the filter cake is taken to obtain a crude collagen product; (7) Add the crude collagen to 0.1 M acetic acid solution and stir to dissolve, then add it to 20% sodium chloride solution and stir again, filter the salting-out product, and take the filter cake to obtain the secondary salting-out collagen wet product; (8) adding the secondary salting-out collagen wet product into a 50-80% ethanol solution, adding biomimetic mineralized apatite in a mass ratio of 1:5-1:1 to the filter cake, and stirring to form mineralized collagen composite fibers; (9) Packing the mineralized collagen complex fibers into freeze-drying molds, pre-freezing at -10 to -20°C, and freeze-drying to obtain block-shaped mineralized collagen complexes; (10) The block-shaped mineralized collagen complex is subjected to vacuum heat cross-linking treatment at 105-140° C. for 2-24 h, and after cooling, it is taken out and mechanically crushed, and sieved to obtain a powdered mineralized collagen complex.
7. The method of claim 5, wherein the biomimetic mineralized apatite is prepared by reacting with collagen in a solution containing calcium and phosphate ions, and then the pH value is adjusted within the range of 9 to 12 to deposit the biomimetic mineralized apatite on the collagen fibers, and the biomimetic mineralized apatite is obtained after washing, freeze-drying and crushing.
8. The method of claim 5, wherein the step of forming the matrix is achieved by melting polyethylene glycol (PEG) and mixing and dispersing the mineralized collagen complex at a temperature of 40-60°C for a period of 10 minutes to 24 hours, depending on the material ratio and the dispersion device.
9. The method of claim 5, wherein sodium carboxymethylcellulose (CMC) is added in powder form to ensure uniform distribution throughout the mixture and the final composition is sterilized before application.
10. The absorbable hemostatic bone graft material of claim 1, wherein the composition further comprises a bioactive agent selected from growth factors, osteoinductive proteins, antimicrobial agents or combinations thereof to enhance bone healing and prevent infection.
11. A method for using the absorbable hemostatic bone graft material of claim 1 in surgery, comprising: (1) Application of bone graft material to bleeding bone surfaces during orthopedic, neurosurgical, or spinal surgery; (2) allowing the material to adhere to the bleeding site, providing hemostasis and supporting bone regeneration; (3) Allow the material to biodegrade over time while being replaced by new bone tissue.